Sox10 is required for Schwann-cell homeostasis and myelin maintenance in the adult peripheral nerve. - Fröb, Franziska; Kichko, Tetyana; Reeh, Peter; Wegner, Michael; et al. (Glia, 2011)
The transcription factor Sox10 functions during multiple consecutive stages of Schwann-cell development in the peripheral nervous system (PNS). Although Sox10 continues to be expressed in mature Schwann cells of the adult peripheral nerve, it is currently unclear whether it is still functional. Here, we used a genetic strategy to selectively delete Sox10 in glia of adult mice in a tamoxifen-dependent manner. The tamoxifen-treated mice developed a severe peripheral neuropathy that was associated with dramatic alterations in peripheral nerve structure and function. Demyelination and axonal degeneration were as much evident as signs of neuroinflammation. Compound action potentials exhibited pathophysiological alterations. Sox10-deleted Schwann cells persisted in the peripheral nerve, but did not exhibit a mature, myelinating phenotype arguing that Sox10 is rather required for differentiation and maintenance of the differentiated state than for survival. Our report is the first evidence that Sox10 is still essentially required for Schwann-cell function in the adult PNS and establishes a useful model in which to study human peripheral neuropathies. © 2011 Wiley-Liss, Inc..
UnivIS-Import:2015-03-09:Pub.2011.med.IB.LPCIPDBI.sox10i
Keywords: Charcot-Marie-Tooth disease; Conditional mouse mutagenesis; Glia; High-mobility-group; Myelin; Peripheral neuropathy; Sry; Transcriptional control